2021
DOI: 10.1186/s12877-021-02019-x
|View full text |Cite
|
Sign up to set email alerts
|

Geriatrician perspectives on perioperative care: a qualitative study

Abstract: Background Perioperative medicine services for older surgical patients are being developed across several countries. This qualitative study aims to explore geriatricians’ perspectives on challenges and opportunities for developing and delivering integrated geriatrics perioperative medicine services. Methods A qualitative phenomenological semi-structured interview design. All geriatric medicine departments in acute public hospitals across Australia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Similar findings of the opinions of operating room nurses were also reported previously. [ 28 29 ] Peñataro-Pintado et al . (2021)[ 30 ] reported that some of the key issues that affected the perioperative nurses’ ability to achieve their duties and guarantee patient safety were the stress of working in the operating room, unsuccessful announcement in the multidisciplinary group, and time pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings of the opinions of operating room nurses were also reported previously. [ 28 29 ] Peñataro-Pintado et al . (2021)[ 30 ] reported that some of the key issues that affected the perioperative nurses’ ability to achieve their duties and guarantee patient safety were the stress of working in the operating room, unsuccessful announcement in the multidisciplinary group, and time pressures.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of geriatricians in Australia and New Zealand [ 88 ] identified a number of barriers to an integrated service including the lack of funding for staffing, encroaching on existing services and competing clinical priorities. The key barrier at the healthcare professional level was the lack of clarity of roles within the perioperative team.…”
Section: Moving Forward and Collaborative Workingmentioning
confidence: 99%
“…Given the care needs of older adults, the American College of Surgeons, American Geriatrics Society, care providers, and healthcare analysts have all called for new models of surgical care to improve the quality of care that older adults receive. 1,[3][4][5][6][7][8][9][10] In response, hospitals worldwide have implemented geriatrics-surgery co-management (GSCM) programs. In this model of care, surgical and geriatric teams partner to provide surgical care aligned with geriatric care principles.…”
Section: Introductionmentioning
confidence: 99%